Ответ:
Пошаговое объяснение:
а) -16-1,4а=-0,9-16
-16+16=-0,9а+1,4а
0=2,3а
а=0/2,3
а=0
б) -х+2,1=-1,2
2,1+1,2=х+х
3=х
х=/
х=
х=3,6
в) 8(-у-2)=-5у-(6-9у)
-8у-16=-5-5+9у
-16+5+6=9у+8у
-5=17у
у=17/(-5)
у= -3,4
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Пошаговое объяснение:
а) -16-1,4а=-0,9-16
-16+16=-0,9а+1,4а
0=2,3а
а=0/2,3
а=0
б) -
х+2,1=
-1,2
2,1+1,2=
х+
х
3
=
х
х=
/![\frac{11}{12} \frac{11}{12}](https://tex.z-dn.net/?f=%5Cfrac%7B11%7D%7B12%7D)
х=![\frac{33*12}{10*11} \frac{33*12}{10*11}](https://tex.z-dn.net/?f=%5Cfrac%7B33%2A12%7D%7B10%2A11%7D)
х=3,6
в) 8(-у-2)=-5у-(6-9у)
-8у-16=-5-5+9у
-16+5+6=9у+8у
-5=17у
у=17/(-5)
у= -3,4